Energy, environment and geopolitics in Eurasia search for security in the water-energy-food nexus - Graham, Norman A. 1948-; Yilmaz, Suhnaz 1971- (Routledge, 2024)
"This book advances our understanding of security and its intricate interactions with geopolitics and the environment in Eurasia. Norman A. Graham and Şuhnaz Yılmaz focus on Eurasia, where the energy-water-food nexus has emerged as a vital aspect of political economy and increasingly as a decisive factor for human security. As clearly revealed during the Russian invasion of Ukraine, this nexus rests on a precarious balance. Graham and Yilmaz argue that Central Eurasia is currently 'Running on Empty' and highlight the key environmental challenges, including water quantity and quality and food security. The authors draw on their extensive fieldwork in countries including Azerbaijan, China, Georgia Kazakhstan, the Russian Federation, Turkey and Uzbekistan to assess the interests and impact of pivotal actors and evaluate the competition and complementarities of these actors regarding water, energy, food security and foreign policy imperatives. They also examine the broader interaction and implications of security at multiple levels by analysing the local, national and international factors in light of geopolitical and environmental challenges. Taking a novel and highly interdisciplinary approach, this book will be an important resource for students and scholars of energy and food security, political economy, international conflict and cooperation and natural resource politics"--
Includes bibliographical references and index
Keywords: Energieversorgung; Lebensmittelversorgung; Wasserversorgung; Ressourcenpolitik; Eurasien; Water-supply / Eurasia; Food supply / Eurasia; Power resources / Eurasia; International economic relations; Security, International / Eurasia; Eurasia / Economic conditions / 21st century